All‐Optical Fine‐Tuning of Absorption Band of Diarylethene with Photochromic Acid‐Generating Spiropyran. Issue 9 (23rd May 2016) - Kusumoto, Sara; Nakagawa, Tetsuya; Yokoyama, Yasushi
Abstract : By taking advantage of p K a difference for the isomers of a spiropyran (MC andSP ), a continuous and reversible shift of the absorption band of the closed form of diarylethene (C ) for 30 nm is successfully realized only by light irradiation and thermal treatment, i.e., without the addition of any chemical species or the application of any physical contact.